From “The Art of the Detail” to “The Continuous Art” (In the Context of the Issue of the Perception of Baroque in the 1920–1930s) - Невская, Дарья (Literatūra, 2016)
The cultures of baroque of the 17th c. and the beginning of the 20th c. are united by the causes of origin (crisis of the world perception, period of transition) and a complex of characteristic features. In the 1920s, Viktor Shklovsky was on the “same one passage of baroque” together with his contemporaries-artists, but in texts of the 1930s the critic blames the same writers and directors with whom he once had been on the same path in “barocalism” (enthusiasm, obsession with baroque). In his critic reviews, Shklovsky defined the contemporary period not only as the period of “ the era of baroque”, but also created the formula of baroque modernism: the world is perceived as cut in to pieces + details and objects prevail, the content + new meaning is ascribed to “ordinary things” + disturbance of balance of artistic elements in a work of art (misrepresentation) = demolition of the united perception of the art work.